The Fate of Residual Fragments After Retrograde Intrarenal Surgery in Long-Term Follow-up - Atis, Gokhan; Pelit, Eyyup Sabri; Culpan, Meftun; Gunaydin, Bilal; Turan, Turgay; Danacioglu, Yavuz Onur; Yildirim, Asif; Caskurlu, Turhan (Urology Journal, 2019)
Purpose: We aimed to describe the natural history of stone fragments ? 7 mm that remained after retrograde intrarenal surgery (RIRS) in long-term follow-up. Materials and Methods: We retrospectively reviewed 142 medical records of patients who had residual fragments (RFs) ? 7 mm after RIRS. Patients were divided into 2 groups according to the size of RFs as ? 4 mm (group 1) and 5 – 7 mm (group 2). Patients’ demographic data, stone characteristics, perioperative data and complications were recorded. Re-growth of RFs, spontaneous passage, renal colic, infection and re-operation rates were our main variables. Result: A total of 142 patients (86 in group 1 / 56 in group 2) were followed for mean 54.45 ± 14.24 and 56.22 ± 10.28 months. Mean size of RFs was 2.85 ± 1.22 mm in group 1 and 6.81 ? 2.21 mm in group 2. Mean number of RFs were 1.1 ± 0.2 in group 1 and 2.4 ± 1.6 in group 2 (P = .035). Spontaneous passage rate of RFs were 30.23% and 17.85% in group 1 and 2, respectively (P = .032). No difference was observed in the re-growth rate of RFs between the two groups (P = .094). Although no difference was observed in re-growth of RFs between the groups, patients in group 2 were more likely to experience stone-related events such as renal colic and re-intervention rate (P = .034, P = .029; respectively). Conclusion: Our results demonstrate that RFs > 4 mm take higher risk in terms of stone-related events and should be followed up more closely.